Sickness absences and losses in productivity-adjusted life years before, during and after the most common orthopedic surgical procedures among employed individuals in Finland - Heiskanen, Jari; Lehtimäki, Aku-Ville; Martikainen, Janne; Ademi, Zanfina; Kostensalo, Joel; Äärimaa, Ville; Lavikainen, Piia (BioMed Central, 2026)
Background
Musculoskeletal diseases requiring surgical procedures in working-age adults impose a significant financial burden on many societies. This observational study focused on evaluating the seven most common elective orthopedic surgeries among the Finnish working-age employed population with an aim to assess the extent of sickness absence accumulation before and after the surgical procedure, along with the duration of hospital stay during treatment. Additionally, the study aimed to quantify productivity-adjusted life years (PALY) and assess the societal economic impact of PALY loss due to sickness absence.
Methods
Data from electronic health records from the Wellbeing Services County of Southwest Finland, Finland, in 2020–2022, compiled with information from national administrative registries, were used to identify working-age, employed patients from seven disease groups (N = 770). Lengths of pre- and post-operative sickness absences together with in-hospital days were calculated, and PALY were estimated over the corresponding periods. Point estimate of the productivity cost of PALY losses was calculated in total and on a per-patient basis based on a reported national average value of one sickness absence day (€344).
Results
The average hospital stay across all patient groups ranged from 1.0 to 5.5 days. The longest pre-operative sickness absence was in lumbar spine fusion (36.7 days), and the shortest in patients with knee ligament injuries (4.3 days). The longest post-operative average sickness absence was for shoulder procedures (114.0 days), and the shortest for carpal tunnel syndrome patients (37.2 days). In all seven patient groups together, on average, 17.4 PALY (27.5% of total PALY loss) were annually lost (corresponding to €2,192,683) in the year before hospitalization, 1.0 (1.6%) PALY annually lost (€194,773) during the hospitalization, and 44.8 (70.9%) PALY annually lost (€5,619,243) in the year after hospitalization. The highest pre-operative per-patient PALY loss in monetary terms was among patients with lumbar spine fusion (€16,693), while the highest post-operative per-patient PALY loss in monetary terms occurred among patients with knee osteoarthritis and knee replacement (€28,673).
Conclusions
The sickness absences were typically longer and PALY losses in monetary terms per patient were higher in the post-operative period compared to the pre-operative period. The seven patient groups examined produced considerable PALY losses and related total productivity costs to the Wellbeing Services County of Southwest Finland. The results of the study call for actions to support a more rapid return to work.